Gamification: Applications for Health Promotion and Health Information Technology Engagement - Marston, H.; Hall, Amanda K. (Handbook of Research on Holistic Perspectives in Gamification for Clinical Practice, 2015)
Game-based approaches (gamification) can provide ideal strategies for health promotion, prevention, and self-management of chronic conditions. However, there is a need to clearly define components and uses of gamification in healthcare for increased patient engagement in health information technology. Therefore, this chapter aims to define gamification and components of gamification, identify relevant research and examples of gamification in regards to health promotion and prevention, discuss strategies to gamify a health application, and summarize current research in the area of gamification for health promotion/prevention. Finally, this chapter provides an overview of gamification applications and how it can be used for health promotion.